From consumer collectives to brand organisations: an online ethnographic study of the formation of human brand organisations in China - Lu, Yifan (2025)
This thesis investigates the formation of human brand organisations within the Chinese context, using Chinese celebrity fans collectives as a starting point and representative examples. Specifically, the research focus on How do Chinese celebrity fans, as consumers of human brands, form their own entities online, and what characteristics do such consumer collectives exhibit? An 18-month online ethnographic study, grounded in symbolic interactionism and grounded theory, addresses key gaps in existing brand community research, including the limited focus on human brands, the unclear distinction between consumer-initiated and company-sponsored communities, and the lack of attention to the early stages of brand community formation.